Isolation of a Genomic Region Affecting Most Components of Metabolic Syndrome in a Chromosome-16 Congenic Rat Model - Šedová, Lucie; Pravenec, Michal; Křenová, Drahomíra; Kazdová, Ludmila; Zídek, Václav; Krupková, Michaela; Liška, František; Křen, Vladimír; Šeda, Ondřej (PloS one, 2016)
Metabolic syndrome is a highly prevalent human disease with substantial genomic and environmental components. Previous studies indicate the presence of significant genetic determinants of several features of metabolic syndrome on rat chromosome 16 (RNO16) and the syntenic regions of human genome. We derived the SHR.BN16 congenic strain by introgression of a limited RNO16 region from the Brown Norway congenic strain (BN-Lx) into the genomic background of the spontaneously hypertensive rat (SHR) strain. We compared the morphometric, metabolic, and hemodynamic profiles of adult male SHR and SHR.BN16 rats. We also compared in silico the DNA sequences for the differential segment in the BN-Lx and SHR parental strains. SHR.BN16 congenic rats had significantly lower weight, decreased concentrations of total triglycerides and cholesterol, and improved glucose tolerance compared with SHR rats. The concentrations of insulin, free fatty acids, and adiponectin were comparable between the two strains. SHR.BN16 rats had significantly lower systolic (18-28 mmHg difference) and diastolic (10-15 mmHg difference) blood pressure throughout the experiment (repeated-measures ANOVA, P < 0.001). The differential segment spans approximately 22 Mb of the telomeric part of the short arm of RNO16. The in silico analyses revealed over 1200 DNA variants between the BN-Lx and SHR genomes in the SHR.BN16 differential segment, 44 of which lead to missense mutations, and only eight of which (in Asb14, Il17rd, Itih1, Syt15, Ercc6, RGD1564958, Tmem161a, and Gatad2a genes) are predicted to be damaging to the protein product. Furthermore, a number of genes within the RNO16 differential segment associated with metabolic syndrome components in human studies showed polymorphisms between SHR and BN-Lx (including Lpl, Nrg3, Pbx4, Cilp2, and Stab1). Our novel congenic rat model demonstrates that a limited genomic region on RNO16 in the SHR significantly affects many of the features of metabolic syndrome.
Keywords: Rats, Inbred BN; Male; potkani inbrední SHR; potkani inbrední BN; mužské pohlaví; metabolický syndrom; lidské chromozomy, pár 16; Hemodynamics; Metabolic Syndrome; Chromosomes, Human, Pair 16; genom; Animals; lidé; Humans; zvířata; Rats, Inbred SHR; Glucose Tolerance Test; Metabolome; Genome; metabolom; hemodynamika; zvířata kongenní; Animals, Congenic; glukózový toleranční test